See the Difference in a Precast Facility: Changing Mindsets with an Experiential Safety Program - Love, Peter; Veli, S.; Davis, P.; Teo, Pauline; Morrison, J. (American Society of Civil Engineers, 2016)
The AU$8.3 billion Sydney Metro Northwest Rail Link is Australia’s largest public transport project and includes the construction of twin 15-km tunnels. A temporary precast facility was constructed to produce the wall-linings for the tunnels. The facility is operated 24 h a day from Monday to Friday and 12 h on Saturday with 100 workers. To enhance the safety performance within the facility, an experiential learning safety program referred to as See the Difference was implemented in conjunction with other safety interventions, although the program was the glue that held all initiatives together. This paper describes the safety program and examines its effectiveness and contribution it made toward reducing incidents and engendering teamwork within the temporary precast facility. It was observed that the See the Difference program had a positive influence on changing the mindset of the workforce from a fixed one to one of growth, which was developed through a process of coaching. The paper draws on actual practice and presents a novel approach to improving safety through the introduction of an experiential safety program. The case study offers a learning opportunity for other organizations that are confronted with implementing safety awareness programs, particularly for infrastructure transportation megaprojects.